A novel hybrid color image encryption algorithm using two complex chaotic systems. (February 2016) - Wang, Leyuan; Song, Hongjun; Liu, Ping
Abstract: Based on complex Chen and complex Lorenz systems, a novel color image encryption algorithm is proposed. The larger chaotic ranges and more complex behaviors of complex chaotic systems, which compared with real chaotic systems could additionally enhance the security and enlarge key space of color image encryption. The encryption algorithm is comprised of three step processes. In the permutation process, the pixels of plain image are scrambled via two-dimensional and one-dimensional permutation processes among RGB channels individually. In the diffusion process, the exclusive-or (XOR for short) operation is employed to conceal pixels information. Finally, the mixing RGB channels are used to achieve a multilevel encryption. The security analysis and experimental simulations demonstrate that the proposed algorithm is large enough to resist the brute-force attack and has excellent encryption performance. Abstract : Highlights: A novel hybrid color image encryption algorithm is proposed. Two complex chaos systems improve the key space greatly. One pixel in a channel may appear in any position and any channel theoretically. Combined encryption processes achieve high security.